ENVIRONMENTAL LITERACY THROUGH THE DISCOVERY LEARNING MODEL: A STUDY AMONG PRIMARY SCHOOL TEACHER EDUCATION STUDENTS AT THE FACULTY OF EDUCATION, UNIVERSITAS NEGERI MAKASSAR - Sahabuddin, Erma Suryani (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research investigates the impact of the Discovery Learning model on the environmental literacy of students in the Primary School Teacher Education Program (PGSD) at the Faculty of Education (FIP), Universitas Negeri Makassar (UNM). Utilizing an experimental quantitative approach, the study evaluates changes in students’ understanding and skills before and after the implementation of a learning model focused on discovery and exploration. The results indicate a significant increase in the average scores from pretest to posttest, as evidenced by descriptive statistical analysis and confirmed through a T-test with a Sig. (2-tailed) value of less than 0.05. These findings affirm that the Discovery Learning model is effective in enhancing students’ environmental literacy, which encompasses not only theoretical knowledge but also critical, analytical, and reflective thinking skills. The practical implications of this research recommend the integration of the Discovery Learning model into the environmental education curriculum, suggesting a more interactive and student-centered learning approach, and highlighting the importance of continuous education and lifelong learning.